Syirkah and Agrarian Disputes Resolution in Toll Construction Projects - Ali, AM. Hasan (UIN K.H. Abdurrahman Wahid Pekalongan, 2024)
Agrarian disputes require resolution. For years, acquiring people’s land for constructing toll infrastructure project still use compensation as the popular term. Philosophically, the term means a reward in the form of money or non-money (in kind) which creates agrarian disputes. The partnership-profit sharing or syirkah offers a win-win solution to solve agrarian disputes. This article used systematic literature review (SLR) approach, which is similar with helicopter view model in looking at the topic of a particular study as a whole by using machine engine system. The aim of using this approach is obtaining complete and comprehensive information that have not been conducted by the previous researches.